Enhancing Employee Performance: A Study on the Impact of Motivation and Work Discipline at the Bone Regency Social Services Office - Rasyid, Muh Nur; Andayaningsih, Sri; Marfianti, Marfianti (Jurnal Ilmu Manajemen Profitability, 2024)
This study aims to (1) To determine the effect of motivation on employee performance at the Social Service Office of Bone Regency (2) To determine the effect of work discipline on employee performance at the Social Service Office of Bone Regency. The sample inthis study was 70 respondents taken from the Social Service Office of Bone Regency. The type of data used in this research is primary and secondary data and this type of research is quantitative research. Data collection was carried out by observation and distributionof questionnaires. Based on the results of data research using calculations through the SPSS version 22 application concerningthe effect of motivation and work discipline on employee performance at the Bone Regency Social Service Office which has been discussed from the previous chapter, the authors draw important conclusions, namely motivation and work discipline have apositive and significant effect on performance employee